2022
DOI: 10.1111/bcp.15516
|View full text |Cite
|
Sign up to set email alerts
|

An allopurinol adherence tool using plasma oxypurinol concentrations

Abstract: Aims This study aimed to develop and evaluate an allopurinol adherence tool based on steady‐state oxypurinol plasma concentrations, allopurinol's active metabolite. Methods Plasma oxypurinol concentrations were simulated stochastically from an oxypurinol pharmacokinetic model for allopurinol doses of 100‐800 mg daily, accounting for differences in renal function, diuretic use and ethnicity. For each scenario, the 20th percentile for peak and trough concentrations defined the adherence threshold, below which im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Direct measurement of medication or metabolites (ie, febuxostat or oxypurinol in allopurinol users) was not done for this study but would be relevant because such measures could be used to more precisely define adherence. 22 As anticipated in a clinical trial, reported adherence was high in the STOP Gout study, with rates approaching those defined using oxypurinol measurement among participants undergoing allopurinol escalation in a previous clinical trial. 22 Collectively, the factors comprising our predictive models demonstrated good discriminative capacity with C-statistics of 0.76 (models excluding adherence) to 0.79 (models including adherence).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Direct measurement of medication or metabolites (ie, febuxostat or oxypurinol in allopurinol users) was not done for this study but would be relevant because such measures could be used to more precisely define adherence. 22 As anticipated in a clinical trial, reported adherence was high in the STOP Gout study, with rates approaching those defined using oxypurinol measurement among participants undergoing allopurinol escalation in a previous clinical trial. 22 Collectively, the factors comprising our predictive models demonstrated good discriminative capacity with C-statistics of 0.76 (models excluding adherence) to 0.79 (models including adherence).…”
Section: Discussionmentioning
confidence: 70%
“…22 As anticipated in a clinical trial, reported adherence was high in the STOP Gout study, with rates approaching those defined using oxypurinol measurement among participants undergoing allopurinol escalation in a previous clinical trial. 22 Collectively, the factors comprising our predictive models demonstrated good discriminative capacity with C-statistics of 0.76 (models excluding adherence) to 0.79 (models including adherence). Accurate prediction could facilitate a more personalized approach in gout management, including the addition of adjunctive therapies or tailoring medications used to treat comorbid disease that might impact SU concentration.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…All participants on dialysis were excluded from the analysis. Data obtained from study visits where the criteria for suboptimal adherence to allopurinol therapy were based on a published allopurinol adherence screening tool 17 were excluded as well as visits with documented low adherence in the study records. The data associated with study visits were excluded if the following data were missing: the dates or times of oxypurinol or urate measurements, dosing information (dose or date), or plasma oxypurinol or serum urate concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…the urine screen. The study highlights the challenges of detecting longitudinal medication-taking behaviour from scant cross-sectional clinical data.The topic of adherence screening was also presented by Smith-Diaz et al14 who developed and evaluated a screening tool to detect allopurinol suboptimal adherence in gout trials. The authors used stochastic simulations from a pharmacometric model for oxypurinol pharmacokinetics (the active metabolite of allopurinol) to determine the threshold plasma concentration below which suboptimal uratelowering taking can be concluded.…”
mentioning
confidence: 99%